2017
DOI: 10.22442/jlumhs.171620520
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge Retention Ability of Undergraduate Medical Students

Abstract: BACKGROUND: Being a natural phenomenon, the knowledge learned by students is quickly forgotten. However, various factors are pertinent for one's memory and knowledge retention ability. This ability is not investigated earlier among pass and fail students of a particular exam. OBJECTIVES: To determine and compare short term memory and Knowledge retention ability among pass and fail students of mid-term exam. METHODS: 103 first-year MBBS students were examined in 3 cycles after result of mid-term examination ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…According to an assessment of knowledge retention ability of undergraduate medical students of year one MBBS UMDC, Karachi, it has been concluded that memory and knowledge retention play an essential role in medical student's grades. The study has suggested the medical education system should be customized in a way where medical students would be able to store knowledge and whatever been taught into their long term memory, which indirectly achieving effective learning (9). Mnemonics are one of the methods to enhance memory consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…According to an assessment of knowledge retention ability of undergraduate medical students of year one MBBS UMDC, Karachi, it has been concluded that memory and knowledge retention play an essential role in medical student's grades. The study has suggested the medical education system should be customized in a way where medical students would be able to store knowledge and whatever been taught into their long term memory, which indirectly achieving effective learning (9). Mnemonics are one of the methods to enhance memory consolidation.…”
Section: Introductionmentioning
confidence: 99%